Moral Action as Cheater Suppression in Human Superorganisms - Aunger, Robert (Frontiers in Sociology, 2017)
Developments in human technology and social organization have enabled the kinds of social roles that individuals can undertake to proliferate – creating a degree of interdependence not seen in other species. Human societies cannot rely on shared genetic interests or dyadic reciprocity to ensure social cohesion because genetic similarity is low while indirect reciprocity is rife; nevertheless, such societies cohere, due to the evolution of novel regulatory mechanisms that inhibit defaulting on social obligations: moral sentiments and actions. While the degree of social cooperation created by these mechanisms remains less than that of the eusocial insects, it is sufficient to suggest that contemporary human societies constitute crude ‘superorganisms’ to which their members have wide-ranging responsibilities. The present paper argues that the domains and extent of moral regulation can be most usefully identified by defining the set of functions required to sustain a human superorganism. These functions are shown to be boundary, production, distribution, storage, control, structure, enforcement, signaling, memory, excretion, perception and reproduction. Moral obligations to act then arise when individuals default on contributing to these functions. Major evolutionary transition theory is used to justify claims as to the crucial aspects of superorganism functioning which enabled human superorganismal groups to form, and thus what aspects of morality had to be developed since the time of our common ancestor with other primates. Finally, comparison is made to Moral Foundations Theory, and the Model of Moral Motives and Dyadic Morality approaches, which suggests that Human Superorganism Theory is simultaneously more parsimonious while being more broadly explanatory. We believe this new approach to defining the moral domain has implications for fields ranging from psychology to legal theory.